Daily Teaching Experiences During Covid19: A Phenomenological Study in Primary Teachers - Jannah, Yunita Miftahul (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study aims to explore the experiences of elementary school teachers in delivering online instruction during the Covid-19 pandemic in Indonesia. Since March 2020, the pandemic has necessitated the implementation of health protocols and social restrictions, compelling teachers to shift abruptly to online teaching. Due to the sudden transition and lack of adequate preparation among teachers, students, and parents, numerous challenges emerged throughout the implementation process. This study uses a qualitative approach with phenomenological data analysis. The number of participants in this study were 4 elementary school teachers who work in SD or MI in East Java. Each participant came from a different school and was selected using a purposive sampling technique. Data were collected through interviews using interview guidelines. The data collected through interviews were then analyzed using interpretive phenomenology. This study uses 4 main themes. The first theme is online teaching experience. The second theme is the barriers to teaching online. The third theme is psychological impact. The fourth theme is addressing the barriers to online learning. The results showed that although teachers encountered many obstacles such as signal factors, quotas, full memory easily, parents who were not technology-savvy, could not do evaluation, felt that they were not optimal in educating.